PEMANFAATAN TEKNOLOGI INFORMASI DALAM MENUNJANG MUTU PENDIDIKAN SEKOLAH - Cindy Putri Nur Azizah; Subiyantoro Subiyantoro (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
PThe use of ICT in learning and school management raises new problems. that is, most teachers are not yet optimal in operating ICT, and many are still not able to keep up with ICT progress. In other words, they are still technologically illiterate. This study aims to add references for this study. The aims of this study were to determine the use of ICT in learning activities and school administration, to understand the role of school principals in developing the use of information technology in school management, and to understand the importance of using information technology in school management. This study uses a descriptive qualitative approach to the type of library research (library research). The data collection technique is carried out by searching literature such as books, journals and other articles that support the writing process. The results of this study are 1) Utilization of ICT in Learning can be included in several ICT-based learning activities, blended e-learning, Web/Blog-based learning, ICT-based assessment, multimedia classes, digital libraries and CBT. 2) To face the industrial revolution 4.0, it must be followed by massive HR development and not be half measures. Therefore, it is necessary. First, an open minded leadership strategy is needed. Second, the presence of the industrial revolution 4.0 requires leaders who are ready to face the unexpected. Third, leaders must react quickly to existing changes. Fourth, leaders must be able to collaborate. 3) technology and information as a basis for data collection plays a very important role in helping to achieve educational goals. If the institution is not supported by quality data and information, it will undoubtedly face obstacles and difficulties, especially in the strategic decision-making process. With this research, it is hoped that it can become a reference source of information regarding the application of Information Technology in learning activities and school administration.